Resilient Surveillance Architecture for Critical Maritime Routes: A Case Study of the Malacca Strait under Extreme Weather Scenarios - Aldy Surya Alriandi; Abdul Rivai Ras; Moch Jurianto (International Journal of Education, Vocational and Social Science, 2025)
The maritime sector’s transition to Maritime 4.0, integrating digital technologies like IoT and AI, enhances operational efficiency but introduces complex cyber-risks. This deep interconnectivity expands the cyber-attack surface, threatening global supply chains, often exploited via human error. Vital chokepoints, such as the Strait of Malacca, face these advanced threats, which are exacerbated by weak governance and regulatory gaps. Concurrently, an escalating marine environmental crisis, driven by intensive maritime activities and climate change (e.g., extreme weather), poses existential threats and operational risks. Current surveillance architectures lack resilience to these extreme weather events, creating dangerous security vacuums. This essay proposes a conceptual framework for a resilient maritime surveillance architecture in the Malacca Strait, integrating proactive risk management, layered redundancy, and adaptive governance. Aligned with the Maritime 5.0 vision and a Sustainable Blue Economy, this framework emphasizes that marine ecosystem health is fundamental to long-term security.